2015
DOI: 10.11604/pamj.2015.20.412.5678
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs associés à la non observance thérapeutique des sujets adultes infectés par le VIH sous antirétroviraux dans un hôpital de référence à Douala

Abstract: IntroductionLe succès du traitement antirétroviral repose sur l'observance. Elle est nécessaire pour réduire la mortalité, diminuer le risque de résistance et restaurer l'immunité. Cette étude a pour but d'identifier et analyser les différents facteurs associés à la non observance thérapeutique des patients infectés par le VIH sous traitement antirétroviraux à l'hôpital de référence Laquintinie de Douala.MéthodesIl s'agit d'une étude transversale et analytique effectuée de mars à juin 2014. La non observance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(37 reference statements)
2
4
0
2
Order By: Relevance
“…In the present study, half of participants were aged between 35 and 45 years. This is similar to some previous studies in which 49.2 and 27.5% aged between 30-44 and 35-44 years, respectively were found (Mbanya et al, 2002;Essomba et al, 2015). These results show that 35 to 45 years are the hardest hit ages as far as HIV infection is concerned in Cameroon.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, half of participants were aged between 35 and 45 years. This is similar to some previous studies in which 49.2 and 27.5% aged between 30-44 and 35-44 years, respectively were found (Mbanya et al, 2002;Essomba et al, 2015). These results show that 35 to 45 years are the hardest hit ages as far as HIV infection is concerned in Cameroon.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the majority of participants were female (70.8%). This result is in line with a previous study carried out in the Laquintinie Hospital in which 64.6% were women, with a sex ratio of 0.54 in favor of women (Ramjee and Daniels, 2013;Essomba et al, 2015). This feminization of the pandemics might be due to the biological, epidemiological and sociocultural factors that characterize women's vulnerability as far as HIV infection is concerned in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 91%
“…Three studies were published in French [116,137,149] and a fluent French speaker was utilized to extract the data and translate into English. The remaining studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that 32.9% of the subjects presented forgetfulness as the main cause of non-compliance. (23) A study conducted in South Korea between 2006 and 2015 found that 30% of the participants stopped taking antiretroviral drugs more than once month due to forgetfulness. (24) In addition to the difficulties identified, the consequence of irregular compliance stand out, such as the drop in defense cells and the hospitalizations due to the worsening of the health condition.…”
Section: Discussionmentioning
confidence: 99%